Intravenous Lidocaine, Amantadine, and Placebo in the Treatment of Sciatica: A Double-Blind, Randomized, Controlled Study. Issue 6 (1st November 1999) - Medrik-Goldberg, Tali; Lifschitz, Daniel; Pud, Dorit; Adler, Rivka; Eisenberg, Elon
Abstract : Background and Objectives: Sciatica is a neuropathic pain syndrome caused by compression and/or inflammation of spinal nerve roots by herniated disc material, and its treatment is therefore usually aimed at reducing compression and inflammation. Studies have shown that both systemic local anesthetics and N -methyl-d-aspartate (NMDA) receptor antagonists may produce analgesia in a variety of neuropathic pain syndromes. The present study evaluated the analgesic efficacy of i.v. infusions of the local anesthetic lidocaine, the NMDA receptor antagonist amantadine, and a placebo in sciatica. Methods: Thirty patients with sciatica, as confirmed by physical examination and imaging studies, were enrolled in a randomized, double-blind, three-arm crossover trial. Infusions of amantadine (2.5 mg/kg), lidocaine (5 mg/kg), and a placebo were administered over a 2-hour period, 2-7 days apart from each other. Spontaneous pain (visual analog scale) and evoked pain (straight leg raise) were measured every 30 minutes for 3 hours. Results: Lidocaine reduced spontaneous pain as compared with amantadine and with the placebo for all measurements and at a significant level at the 30 ( P < .05), 120, and 180 ( P < .01) minute time points. Maximal pain reduction from the baseline was 62 ± 7% for lidocaine, 43 ± 7% for amantadine, and 47 ± 7% for the placebo. Straight leg raise test also significantly improved with lidocaine (from 30 to 37°; P < .05), as compared to amantadine (34-36°) and to the placebo (32-34°). All three treatments were relatively well tolerated. Conclusions: Intravenous lidocaine, rather than amantadine, reduces both spontaneous and evoked sciatic pain.